Proguithera caspersi, a new cavernicolous thread-legged bug species (Hemiptera: Heteroptera: Reduviidae: Emesinae) from Hainan, China - Chen, Zhuo; Li, Hu; Cai, Wanzhi (Zootaxa, 2021)
The thread-legged bug genus Proguithera Wygodzinsky, 1966 is recorded from China for the first time, and a new species, P. caspersi sp. nov., is described and illustrated. The new species is cavernicolous and was collected on the walls of a cave together with another emesine species Myiophanes tipulina Reuter, 1881. The type species of the genus, P. drescheri (Wygodzinsky, 1966), is re-diagnosed based on the examination of the holotype. An updated key to species of the Guithera–Lutevula genus group is provided.